An anatomical appraisal of dynamic muscle transfer of the orbicularis oculi muscle. Issue 1 (January 2022) - Aftab, Raiyyan; Bibby, Pandora; White, Pamela; Swamy, Meenakshi; Patten, Debra; Saleh, Daniel B.
Summary: Facial nerve palsy can cause significant distress for patients. We investigated the innervation of the orbicularis oculi muscle (OOM) and assessed the viability of unipedicle contralateral muscle transfer to restore symmetrical and spontaneous blinking. Cadaveric dissection and measurements were performed on lite fixed cadavers ( n = 15). Medial innervation of the OOM was identified prior to raising and transposing a flap to the contralateral eyelid. Measurements were performed in-situ and following transposition. A medial ascending branch of the buccal nerve innervating the OOM was identified bilaterally in all cadavers. The average length of flap raised was 59.85 mm (± 4.69 mm) with no difference between the left and right. Flaps with pedicles not dissected off the bone covered 48% of the ciliary margin length (CM) and 62% of the palpebral length (PL). Flaps dissected off the bone covered 72% of the CM and 92% of the PL. The results demonstrate that a flap can theoretically transpose to >50% of the contralateral eyelid length. Increased coverage of the eyelid was achieved by releasing the pedicle from the underlying bone. Little attention was focused on buccal innervation of the eyelids, and this consistent medial pattern may allow an innervated flap transfer to restore symmetrical blinking, something that eludes modern paralysis surgery in a single-stage procedure.